A gestão democrática na escola municipal: o conselho escolar em questão - Vargas, Ana Lúcia Silva (2018)
The theme of this dissertation was highlighted as "The spaces of democracy in the Municipal System of Education", having as a field of research the School Council of municipal public schools in the Municipality of Alegrete, based on the problem: what limits and possibilities of realization of a participatory democracy in the School Councils as public spaces of social representativeness in school management? In this perspective, the general objective was to analyze the School Councils in municipal schools in Alegrete as spaces of democracy and participation in the Municipal Education System, based on their conceptions and actions. The specific objectives were: To investigate the spaces of exercise of democracy existing in the politico-social and economic reality; To investigate conceptions and forms of action of the Municipal Education System in the perspective of the democratization of the collegiate bodies; Identify functions and attributions of School Councils as spaces for the exercise of democracy in school reality; To investigate to what extent the participation of the school community occurs in the process of decision making in the School Council of four schools of the Basic Education of the municipal network; Apply in the municipal school, here denominated School A, the intervention project, taking the School Council as object of the research. For the development of this research, the Case Study was used as a qualitative research method, starting with a literature review pertinent to the subject. For the collection of data were used the Documentary Research and Questionnaires and for the intervention project, the debate took place through the Focus Group. The subjects of the research were the members of the School Council of 4 schools of the Municipal Network, who answered the questionnaire. At School "A" the Focus Group was held and a training course was developed for the school community, which was the product of this Professional Master's Degree. The results of these activities evidenced that the great challenge is to achieve greater effectiveness in the participation and co-responsibility of the participants of the School Councils in a democratic perspective, which implies in the search of the interests of the diverse segments involved and greater transparency and legitimacy in the decisions taken, contributing for the formation of all from a citizen perspective, in spaces of democracy in the school community.